2012
DOI: 10.1007/s12603-011-0345-5
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in relation to postural stability in the elderly

Abstract: Low levels of vitamin D were associated with PI. This association could also have an effect on slow GV and increased risk of falls. In conclusion, using an objective method to measure balance in older fallers we have identified a novel role of vitamin D in balance control. Prospective studies are required to confirm the effect of vitamin D on PI and elucidate the mechanisms of this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 22 publications
0
21
2
1
Order By: Relevance
“…These results may have been influenced by the ages of the volunteers, even in a homogeneous sample regarding age. Some studies of patients who were older than those in our group found that postural instability is associated with low vitamin D concentrations 9 and the postural balance parameters can be improved with exercise intervention after three months 21. However, in another study, vitamin D supplementation did not improve physical function in older individuals 22.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…These results may have been influenced by the ages of the volunteers, even in a homogeneous sample regarding age. Some studies of patients who were older than those in our group found that postural instability is associated with low vitamin D concentrations 9 and the postural balance parameters can be improved with exercise intervention after three months 21. However, in another study, vitamin D supplementation did not improve physical function in older individuals 22.…”
Section: Discussioncontrasting
confidence: 51%
“…Vitamin D is associated with muscular health 7 and contributes to the maintenance of muscle strength during ageing 5,8. Higher serum vitamin D concentrations have also been associated with greater muscle strength in healthy older individuals 4,5 who have suffered falls 9 and in those who have osteoporosis 6. However, these findings are currently being debated in the literature 10,11.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28] Several studies have found a significant positive association between vitamin D deficiency and slower gait speed when walking (i.e., single tasking). [122][123][124][125][126] Although we found worse executive function in vitamin D insufficient subjects, we did not find a significant correlation between single gait velocity and vitamin D levels nor a difference in single gait velocity between vitamin D insufficient and sufficient groups. Executive dysfunction is sometimes present even in the absence of global cognitive impairment, and it may be present in the older adult before gait impairments are evident.…”
Section: Discussioncontrasting
confidence: 84%
“…121,122 Interestingly, age-related decline in executive function is common among elderly [123][124][125] , and it has been associated with an increased fall risk and gait impairments, including slower gait speed, even with no obvious cognitive impairments. 122,[126][127][128][129][130][131][132][133][134][135] With aging the ability to perform automatic tasks, such as walking, becomes harder and more cognitively demanding. 80 According to recent evidence, age-related deficits in mobility might be partially compensated by effortful higher order cognitive strategies involving executive function that replace the automated sensorimotor processing.…”
Section: Vitamin D Deficiency Cognitive Impairment and Executive Dymentioning
confidence: 99%
“…Reasons for this are that lifestyles for many older people, particularly women, are increasingly associated with indoor activities and with foods not being fortified for vitamin D in Australia. Taken together, there is a high prevalence of vitamin deficiency in this particular Western Sydney population (45%),29 thus a high level of vitamin D supplementation is required in this population. In Colombia, the falls clinic prioritized gentle balance exercise interventions at home due to the fact that despite 98% of Colombian older adults know about the benefits of exercise only 5% exercise every day 30.…”
Section: Discussionmentioning
confidence: 99%